Citizens against Austerity: a Comparative Reflection on Plataforma de Afectados por la Hipoteca (PAH) and Bündnis Zwangsräumung Verhindern (BZV) - Ordóñez, Vicente; Feenstra, Ramón A.; Tormey, Simon (Araucaria, 2015)
Despite significant socioeconomic differences between Spain and Germany, the two countries have witnessed the growing presence of activist initiatives addressing housing problems. Plataforma de Afectados por la Hipoteca (PAH) in Spain and Bündnis Zwangsräumung Verhindern (BZV) in Berlin are struggling to stop evictions and defend citizens’ housing rights. The goal of this paper is to reflect on how politics are developing in relation to austerity and the lack of basic goods for parts of the population. This paper adopts a qualitative methodology based on a comparative case study of PAH and BZV to study the similarities and differences between the two platforms. The paper focuses especially on PAH and BZV ideological and sociological backgrounds, political repertories and political logics.